PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA PEMBELAJARAN KONSEP ROUTING DALAM MATA KULIAH TEKNIK JARINGAN - Raulia Putri, Diva; Anugrah, Septriyan; Kurnia, Reni; Masnur, Alkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students' difficulties in grasping abstract routing concepts. The learning process, which remains dominated by standard presentation media and constrained by limited instructional time, hinders students' ability to visualize routing processes. This study aimed to develop valid and practical augmented reality learning media for teaching routing concepts. It employed the Research and Development (R&D) method using the 4D model, comprising the Define, Design, Develop, and Disseminate stages. A practicality test was conducted with 23 students from the Educational Technology study program. Data collection instruments included validation sheets for subject matter experts and media experts, as well as a practicality questionnaire. The results indicate that the developed augmented reality learning media achieved a 96% validation score from the subject matter expert (categorized as